Applications of functionally graded materials in optoelectronic devices - Wośko, Mateusz; Paszkiewicz, Bogdan; Piasecki, Tomasz; Szyszka, Adam; Paszkiewicz, Regina; Tłaczała, Marek (Oficyna Wydawnicza Politechniki Wrocławskiej, 2005)
Up to now research on functionally graded materials (FGM) was focused on their mechanical and strength properties. The paper presents a review of possible applications of AIII–BV group materials with graded composition for optoelectronic devices, such as p-i-n diodes, heterojunction photodetectors and lasers. Nowadays, there are no optoelectronic devices fabricated from FGM. The theoretical simulation showed that devices with FGM active region would have superior characteristics compared with classical constructions.
Optica Applicata, Vol. 35, 2005, nr 3, s. 663-667
Keywords: optyka; functionally graded materials (FGM); functionally graded materials; AIII–BV; optoelectronic